Rapid Physiological Fluctuations in Nucleus Accumbens Oxygen Levels Induced by Arousing Stimuli: Relationships with Changes in Brain Glucose and Metabolic Neural Activation - Solis Jr., Ernesto; Cameron-Burr, Keaton T.; Kiyatkin, Eugene A. (Frontiers in Integrative Neuroscience, 2017)
Proper entry of oxygen from arterial blood into the brain is essential for maintaining brain metabolism under normal conditions and during functional neural activation. However, little is known about physiological fluctuations in brain oxygen and their underlying mechanisms. To address this issue, we employed high-speed amperometry with platinum oxygen sensors in freely moving male rats. Recordings were conducted in the nucleus accumbens (NAc), a critical structure for sensorimotor integration. Rats were exposed to arousing stimuli of different nature (brief auditory tone, a 1-min novel object presentation, a 3-min social interaction with a conspecific, and a 3-min tail-pinch). We found that all arousing stimuli increased NAc oxygen levels. Increases were rapid (4-10-s onset latencies), modest in magnitude (1-3 M or 5-15% over baseline) and duration (5-20 min), and generally correlated with the arousing potential of each stimulus. Two strategies were used to determine the mechanisms underlying the observed increases in NAc oxygen levels. First, we showed that NAc oxygen levels phasically increase following intra-NAc microinjections of glutamate that excite accumbal neurons. Therefore, local neural activation with subsequent local vasodilation is involved in mediating physiological increases in NAc oxygen induced by arousing stimuli. Second, by employing oxygen monitoring in the subcutaneous space, a highly-vascularized area with no metabolic activity, we determined that physiological increases in NAc oxygen also depend on the rise in blood oxygen levels caused by respiratory activation. Due to the co-existence of different mechanisms governing oxygen entry into brain tissue, NAc oxygen responses differ from fluctuations in NAc glucose, which, within a normal behavioral continuum, are regulated exclusively by neuro-vascular coupling due to glucose’s highly stable levels in the blood. Finally, we discuss the relationship between physiological fluctuations in NAc oxygen and metabolic brain activation assessed by intra-brain heat production.